Caution at choosing a particular colony‐forming unit from faecal Escherichia coli: it may not represent the sample profile. (1st March 2020) - Maciel, J.F.; Gressler, L.T.; da Silveira, B.P.; Dotto, E.; Balzan, C.; Matter, L.B.; Siqueira, F.M.; de Vargas, A.P.C.
Abstract: Data about phylogenetic classification of Escherichia coli colonizing calves, lambs and foals are routinely neglected and restricted to outdated methodologies, even in the context of antimicrobial susceptibility (AS) testing. Thus, the aim of this study was to determine the phylogenetic diversity and the AS profile of E. coli colony‐forming units (CFUs) from faecal samples of healthy animals. Five CFUs of E. coli were randomly selected from each faecal culture of calves ( n = 13), foals ( n = 13) and lambs ( n = 13), totalizing 195 CFUs phylo‐typed by quadruplex PCR. The AS profile of five CFUs from 15 samples (five from each animal species; n = 75 isolates) against nine drugs was determined by agar diffusion test. We found E. coli belonging to all phylo‐groups already described, except D group, with the predominance of B1 (65% CFUs; 126/195) in the three‐animal species sampled. Most faecal samples of calves (77%; 10/13) and foals (69%; 9/13) harboured both pathogenic and nonpathogenic E. coli . All faecal samples showed CFUs with diverse AS profile, highlighting the ineffectiveness of tetracycline, sulphonamide and ampicillin. As a key point, our data reinforce the importance to select at least four E. coli CFUs for AS testing. Significance and Impact of the Study: This study provides relevant data about the high phylogenetic and antimicrobial susceptibility diversity observed in Escherichia coli colony‐forming units (CFUs) from a bacteriological culture of faeces from healthy calves, foals and lambs. The selection pressure exerted by the herd treatment may directly impact the intestinal microflora of animals that have never been treated. Finally, we emphasize the importance of Clinical Laboratory Standards Institute guidelines and we recommended to analyse at least four E. coli CFUs to determine, in particular, the antimicrobial susceptibility profile of faecal isolates, independent of the animal's health status.